Decreased Time From Human Immunodeficiency Virus Diagnosis to Care, Antiretroviral Therapy Initiation, and Virologic Suppression during the Citywide RAPID Initiative in San Francisco. (25th May 2020) - Bacon, Oliver; Chin, Jennie; Cohen, Stephanie E; Hessol, Nancy A; Sachdev, Darpun; Coffey, Susa; Scheer, Susan; Buchbinder, Susan; Havlir, Diane V; Hsu, Ling
Abstract: Background: Early virologic suppression (VS) after human immunodeficiency virus (HIV) infection improves individual health outcomes and decreases onward transmission. In San Francisco, immediate antiretroviral therapy (ART) at HIV diagnosis was piloted in 2013–2014 and expanded citywide in 2015 in a rapid start initiative to link all new diagnoses to care within 5 days and start ART at the first care visit. Methods: HIV providers and linkage navigators were trained on a rapid start protocol with sites caring for vulnerable populations prioritized. Dates of HIV diagnosis, first care visit, ART initiation, and VS were abstracted from the San Francisco Department of Public Health HIV surveillance registry. Results: During 2013–2017, among 1354 new HIV diagnoses in San Francisco, median days from diagnosis to first VS decreased from 145 to 76 (48%; P  < .0001) and from first care visit to ART initiation decreased from 28 to 1 (96%; P  < .0001). By 2017, 28% of new diagnoses had a rapid start, which was independently associated with Latinx ethnicity (AOR, 1.73; 95% CI, 1.15–2.60) and recent year of diagnosis (2017; AOR, 16.84; 95% CI, 8.03–35.33). Persons with a rapid ART start were more likely to be virologically suppressed within 12 months of diagnosis than those with a non-rapid start (RR, 1.17; 95% CI, 1.10–1.24). Conclusions: During a multisector initiative to optimize ART initiation, median time from diagnosis to VS decreased by nearly half. Immediate ART at care initiation was achieved across many, but not all, populations, and was associated with improved suppression rates. Abstract : During a collaborative, multisector initiative to optimize the time to achieving virologic suppression, the median time from diagnosis to virologic suppression and time from first care visit to antiretroviral therapy initiation dramatically decreased and the likelihood of virologic suppression increased.